A LITERATURE REVIEW ON THE IMPACT OF PSYCHOEDUCATION ON MEDICATION ADHERENCE, EMOTIONAL STABILITY, AND QUALITY OF LIFE INBIPOLAR DISORDER - Fitrio Deviantony; Robby Prihadi Aulia Erlando; Salwa Nirwanawati (Universitas Kusuma Husada Surakarta, 2026)
Background: Bipolar disorder (BD) is a chronic psychiatric condition characterized by recurrent mood episodes that significantly impair psychosocial functioning and quality of life. Alongside pharmacological treatment, psychoeducation is recognized as an essential non-pharmacological intervention that enhances illness awareness, supports self-management, improves medication adherence, and facilitates early detection of relapse warning signs.Aim: This literature review aims to examine the effectiveness of psychoeducational therapy in the management of bipolar disorder, focusing on relapse prevention, medication adherence, emotional stability, and quality of life.Methods: A literature review was conducted using studies published between 2020 and 2024 and retrieved from Google Scholar and PubMed databases. The search utilized keywords such as “psychoeducational non-pharmacological therapy” and “bipolar disorder.” Included studies comprised randomized controlled trials, quasi-experimental studies, cohort studies, and systematic reviews.Results: The findings indicate that psychoeducation plays a significant role in improving both clinical and psychosocial outcomes in individuals with BD. Psychoeducational interventions consistently reduced relapse rates, improved medication adherence, enhanced emotional stability, and strengthened patients’ and families’ coping abilities. Family-based and culturally adapted approaches further increased treatment engagement and reduced caregiver burden.Conclusion: Psychoeducation is a vital adjunct to pharmacological treatment in bipolar disorder management, contributing to sustained symptom control and improved quality of life.